Oxidative Transformations in Aqueous Medium by Cerium Based Phase-Transfer Oxidant Impregnated on Fumed Silica - Dewan, Anindita; K. Kakati, Dilip (Asian Journal of Chemistry, 2010)
A simple, convenient, inexpensive and environmentally benign oxidative transformation of alcohol and oxime in aqueous medium to their corresponding carbonyl compounds by cerium based phase-transfer oxidants impregnated on fumed silica is presented.